Variability of biological traits of Bulinus truncatus and Biomphalaria pfeifferi, the intermediate host snails of schistosomiasis, from three climatic zones of Côte d’Ivoire - Diakité, Nana R.; Koffi, Patricia B.; Konan, Cyrille K.; Bassa, Fidèle K.; Chamberlin, Andrew J.; Ouattara, Mamadou; De Leo, Giulio A.; N’Goran, Eliezer K. (Frontiers in Environmental Science, 2023)
Background: Schistosomiasis is endemic throughout all regions of Côte d'Ivoire, however, species of the intermediate snail host vary across bioclimatic zones. Hence, a deeper knowledge of the influence of climatic on the life history traits of the intermediate snail host is crucial to understand the environmental determinants of schistosomiasis in a rapidly changing climate. The aim of this study was to run a common garden experiment to assess differences in survival, somatic growth and fecundity of both Bulinus truncatus and Biomphalaria pfeifferi snails collected in three different bioclimatic areas.: A cross-sectional malacological survey was conducted in February 2021 in the south, center and north of Côte d'Ivoire. We sampled two populations of B. truncatus, the intermediate host snail of This is a provisional file, not the final typeset article Schistosoma haematobium, from northern and central Côte d'Ivoire, and two populations of Bi. pfeifferi, the intermediate host snail for Schistosoma mansoni, from the southern and central regions.Snails collected at the human-water contact sites were brought in the laboratory where they reproduced.The first generation snails (G1) for each population were reared under the same laboratory conditions, i.e., at 24-26C, during 63 days (9 weeks), to estimate survival, growth, and fecundity.We found that G1 Bulinus snails from the north population showed higher survival and growth rates during our study and higher number of eggs at first reproduction, compared to the ones from the central region. For Bi. pfeifferi, no significant difference in survival rate was observed between snails from the southern and central populations, whereas those from the south exhibited higher growth rates and higher number of eggs per individual at first reproduction than G1 snails from the central population.Our study provides evidence for heterogeneity in snails' life-history traits in response to temperature among the populations from the three climatic regions. Further experiments from multiple populations are needed to confirm that snails express traits that, under optimal conditions, can lead to expansion of their geographical range and hence an increase in the risk of schistosomiasis transmission.Transplantation experiments will be required to assess implications of the changing climate on snails' persistence, distribution and abundance.